A critical Fanonian understanding of black student identities at Rhodes University, South Africa,Critical fanonoan understanding of black student identities at Rhodes University, South Africa - Mercadal-Barroso, Adriana Kimberly (Rhodes University, Faculty of Humanities, Department of Sociology, 2015)
South African history is rooted in racial identities, inequalities and injustices, which the post-apartheid government has sought to address for twenty years since 1994. The transition to a post-apartheid society though has been a difficult one with the social structure and everyday life still marked by the racial past. Though racial classifications on an official basis no longer exist, racial identities continue to pervade the country. Of particular significance to this thesis are black identities including the possibility of black inferiority, which I examine in relation to black post-graduate university students in contemporary South Africa, specifically at Rhodes University. In examining this topic, I draw extensively on the work of Frantz Fanon, who wrote about both colonial society and the emerging post-colonial experience. Fanon was a young black intellectual whose work was in part based on his own experiences of being a once-colonised black person in a world which he perceived as being dominated by whiteness. In his work he expresses his own perceptions of whiteness and how the black identity has come to be shaped by and around this dominant white foundation. Fanon extensively discussed the lives of black intellectuals and elites, and demonstrated how the black identity becomes shaped by and around the world of whiteness. In doing so, he raised a range of themes, such as black inferiority, mimicry and double consciousness. I draw upon the work of Fanon in a critically sympathetic manner to delve into the experiences of black postgraduate students as they negotiate their way through a university setting dominated by a white institutional culture. I bring to the fore the argument that the racial identities of these students is not fixed and sutured but, rather, is marked by considerable fluidity and ambiguity such that black identity must be understood not just as a state of being but also as a process of becoming.
Keywords: Fanon, Frantz, 1925-1961 -- Political and social views; Rhodes University; Education, Higher; College graduates, Black -- South Africa -- Grahamstown -- Attitudes; Identity; Black people -- Ethnic identity